Perancangan Pusat Kecantikan dan Kebugaran dengan Konsep Asitektur Modern di Ancol, Jakarta Utara - Siska Apriyati; Karya Subagya; Anggraeni Dyah S. (MAESTRO, 2020)
Activities and patterns of life that are full of competition in the city of Jakarta affect the needs of women and men for the psychological and non-psychic care infrastructure. At present the beauty and fitness center which tends to be more dominant is in a separate place, so that women and men cannot get maximum psychological and non-psychic care easily and are well facilitated. To complement the beauty and fitness facilities in the city of Jakarta, a beauty and fitness center design was made by providing a place for complete relaxation between the beauty center and the fitness center in the same area, with buildings that apply modern architectural concepts. Application of Modern Architecture in the Design of Beauty and Fitness Centers in Ancol, North Jakarta based on conformity to the function of buildings that prioritizes technology and lifestyle of people in the modern era who tend to want more quickly, efficiently and practically. The concept of modern architecture is applied to the site, the shape of the building, and the use of materials as well as the uniformity of the shape of the buildings within the Beauty and Fitness Center area in order to create good harmony.